Aaa 3
Aaa 3
Aaa 3
( P R O V I N G , VA L I D AT I O N A N D V E R I F I C AT I O N E T C . )
WHAT IS MATHEMATICAL INDUCTION?
Mathematical induction is a powerful, yet straight-
forward method of proving statements whose
domain is a subset of the set of integers.
Usually, a statement that is proven by induction is
based on the set of natural numbers.
This statement can often be thought of as a function
of a number n, where n = 1, 2, 3,. . .
Proof by induction involves three main steps
Proving the base of induction
Forming the induction hypothesis
Proving that the induction hypothesis holds true for all
numbers in the domain.
WHAT IS MATHEMATICAL INDUCTION?
Let P(n) be the predicate defined for any positive
integers n, and let n0 be a fixed integer. Suppose the
following two statements are true
1. P(n0) is true.
2. For any positive integers k, k n0, if P(k) is true
then P(k+1)is true.
If both of the above statements are true then the
statement:
n N, such that n n0, P(n) is also true
STEPS IN PROVING BY INDUCTION
2. Inductive hypothesis
Assume formula is true for an arbitrary n = k
where, k Z+ and k n0
3. To Prove Claim
Show that formula is then true for k+1
Basis step.
Show that proposition P(1) is true.
Inductive step.
Show that for every positive integer n, the
implication P(n) → P(n+1) is true.
P(n) for a fixed n is called inductive hypothesis.
Basis Step
First suppose that we have a proof of P(0).
Inductive Hypothesis
k > 0, P(k) P(k + 1)
How it is proved n > 0?
P(0) P(1)
P(1) P(2)
P(2) P(3)
...
Iterating gives a proof of n, P(n). This is another way of
proving validity of mathematical Induction.
PROOF BY INDUCTION
VALIDITY OF PROOF
Another Easy Example
REASONING
Example 2 OF PROOF
Use Mathematical Induction to prove that sum of the first n odd
positive integers is n2.
n
( 2
i =1
i − 1) = n 2
Proof
Let P(n) denote the proposition that
Basis step : P(1) is true , since 1 = 12
Inductive step : Let P(k) is true for a positive integer k,
i.e., 1+3+5+…+(2k-1) = k2 = (k+1)2
Note that: 1+3+5+…+(2k-1)+(2k+1) = k2+2k+1= (k+1)2
∴ P(k+1) true, by induction, P(n) is true for all n Z+
Another Proof
n n
(
i =1
2i − 1) = 2 i − n
i =1
= n ( n + 1) − n =n 2
Understanding of the last example
REASONING OF PROOF
2
Use Mathematical Induction to prove that sum of the first n odd positive integers is n .
{1,3,5,7,….,2n-1}= set of n odd integers=S(n)
Prove 1+3+5+7+……….+(2n-1)=n2
S(n)= n2
1. Base case: n=1
S(n)=1=12 So, first case is true.
2. Inductive case: Assume that S(n)=n2,It should be true for S(n+1)=(n+1)2
1+3+5+……..+(2n-1)
= 1+3+5+……..+(2n-1)+(2(n+1)-1)
=1+3+5+…….. +(2n-1)+(2n+2-1)
=1+3+5+…….. +(2n-1)+(2n+1)
S(n+1)= 1+3+5+7+……..+(2n+1)=S(n)+2n+1.
By,
S(n+1)=n2+2n+1=(n+1)2
S(1)=1
S(n)=n2
S(n+1)=(n+1)2
Proving Inequalities
REASONING OF PROOF
Example 3
Use mathematical Induction to prove that the
inequality
n < 2n for all n Z+
Proof
Let P(n) be the proposition that n < 2n
Basis step : P(1) is true since 1 < 21 .
Inductive step :
Assume that P(n) is true for a positive integer n = k,
i.e., k < 2k.
Now consider for P(k+1) :
Since, k + 1 < 2k + 1 2k + 2k = 2.2k = 2k + 1
∴ P(k+1) is true.
It proves that P(n) is true for all n Z+.
UNDERSTANDING OF LAST EXAMPLE
n<2n
Base case: n=1
1<2 P(1) the base case is true.
Inductive case: n=k
k<2k
Multiply both sides by 2
2k <2.2k
k+k< 2k+1
Hypothesis: n=k+1
K+1< 2k+1
Sidenotes k>1
k+k>k+1
k+1<k+k k+1< k+k < 2k+1
Example 4: Harmonic Numbers
The harmonic numbers Hk, k = 1, 2, 3, …, are
defined by H k = 1 + 1 + 1 + ... + 1
2 3 k n
Use mathematical induction to show that H 2n 1 +
2
whenever n is a nonnegative integer.
Proof
Let P(n) be the proposition that H 2n 1 + n / 2
Basis step :
P(0) is true, since, H 20 = H1 = 1 1 + 0 / 2 = 1
Inductive step
Assume that P(k) is true for some k, H 2k 1 + k / 2
Example 4: Harmonic Numbers
Now consider
1 1 1 1 1 1
H 2k +1 = 1 + + + + k + k + k + + k +1 k k
2 3 2 2 +1 2 + 2 2 =2 +2
1 1 1
= H 2k + k + k + + k +1
2 +1 2 + 2 2
k 1 1 1
(1 + ) + k + k + + k +1
2 2 +1 2 + 2 2
k 1 1 1
(1 + ) + k + k ++ k
2 2 +2 k
2 +2 k
2 + 2k
k 2k k 1 k +1
= (1 + ) + k k = 1+ + = 1+
2 2 +2 2 2 2
∴P(k+1) is true.
Hence the statement is true for all n Z+.
Strong Mathematical Induction
Strong Mathematical Induction
Let P(n) be a predicate defined for integers n, and a
and b are fixed integers with a ≤ b.
Suppose the following statements are true:
1. P(a), P(a + 1), … , P(b) are all true
(basis
step)
2. For any integer k > b,
if P(i) is true for all integers i with a ≤ i < k,
then P(k) is true. (inductive
step)
Then P(n) is true for all integers n ≥ a.
Example 1: Divisibility by a Prime
Theorem:
For any integer n ≥ 2, n is divisible by a prime.
Proof
(by strong mathematical induction):
Basis step:
The statement is true for n = 2. This is because 2 | 2 and 2 is a prime
number.
Inductive step:
Assume the statement is true for all i with 2 ≤ i <k (inductive hypothesis)
;
To show that it is true for k .
Example 1: Divisibility by a Prime
Proof :
Let P(n) n can be written as the product of primes.
Basis : P(2) is true, since 2 is the first prime number
Inductive : Assume that the statement is true for n = k, i.e.
P(2), P(3), …, P(k) can be written as product of primes.
Prove that: true for n = k, i.e. P(k + 1) is product of primes.
Case 1 : k + 1 is prime, then nothing to prove
Case 2 : k + 1 is composite, then
k + 1 = xy, where 2 x y < k+1
Inductive hypothesis, a and b are product of primes.
Hence P(k+1) can be written as product of primes.
Any Amount Limited Coins: More Steps in Basis
Statement
Show that any amount in cents ≥ 8 cents can be
obtained using 3 cents and 5 cents coins only.
Proof
We have to prove that, amount = 3.m + 5.n, m 0, n
0
Basis Step
This time check for a five particular values:
8 = 1.3 + 1.5
9 = 3.3
10 = 2.5
11 = 2.3 + 1.5
12 = 4.3
Now we generalize it?
Any Amount Limited Coins : More Steps in Basis
Let P(n) be the statement that:
“n cents can be obtained using 3 and 5 cents”.
Inductive Hypothesis
We want to show that
P(k) is true P(k+1), k ≥ 8
Proof
( )
Basis step: Since, A1 A2 = A1 A2 true for n = 2
Induction step: Assume the result is true n = k and then prove for n = k+1.
k +1 k
A j = A j Ak +1
j =1 j =1
k
= A j Ak +1
j =1
k
= A j Ak +1 (by induction hypothesis)
j =1
k +1
= Aj
j =1
Base case n=2
2 2
Aj = Aj
j =1
j =1
(A A 1 2 = A1 A2 )
Inductive Step
n=k
k k
Aj = Aj
j =1
j =1
( A A ... A
1 2 k = A1 A2 ... Ak )
n = k +1
k +1 k
Aj = Aj Ak +1
j =1 j =1
( A A ... A A )
1 2 k k +1
Postage Ticket: Again More Steps in Basis
Prove that postage ticket of amount 12 cents can be formed
using only 4 cent and 5 cent stamps.
Proof
Let P(n) n cents can be formed using only 4 and 5 cent
P(n) n = 4s + 5t s 0, and t 0 n 12
Basis : P(12) is true, since 12 = 4 3;
P(13) is true, since 13 = 4 2 + 5 1;
P(14) is true, since 14 = 4 1 + 5 2;
P(15) is true, since 15 = 5 3;
Inductive : Assume P(12), P(13), …, P(k) are true.
Now prove for P(k + 1) (k−3 12)
Suppose k-3 = 4 s + 5 t.
Then k +1 = 4 (s + 1) + 5 t. true for n = k + 1.
By Strong Induction, P(n) is true if n Z and n 12.
Proving a Property of a Sequence
Proposition:
Suppose a0, a1, a2, … is defined as follows:
a0 = 1, a1 = 2, a2 = 3,
ak = ak-1 + ak-2 + ak-3 for all integers k ≥ 3.
Then an ≤ 2n for all integers n≥0. P(n)
Proof (by strong induction)
Basis step:
The statement is true
for n = 0: a0 = 1 ≤ 1 = 20 P(0)
for n = 1: a1 = 2 ≤ 2 = 21 P(1)
for n = 2: a2 = 3 ≤ 4 = 22 P(2)
Proving a Property of a Sequence
Inductive step:
For any k > 2, assume P(i) is true for all i with 0 ≤ i < k, i.e.,
ai ≤ 2i for all 0 ≤ i < k (1)
Show that
P(k) is true: ak ≤ 2k (2)
Now consider
ak = ak-1 + ak-2 + ak-3
≤ 2k-1 + 2k-2 + 2k-3 based on (1)
≤ 20 + 21 + … + 2k-3 + 2k-2 + 2k-1
= 2k - 1 ≤ 2k
Thus, P(n) is true by strong mathematical induction.
Hence it proves the result
Existence of Binary Integer Representation
Theorem
Given any positive integer n, there exists a unique representation of
n in the form:
n = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
Where r is non-negative integer
cr.= 1, and cj = 0 or 1, j = 0, 1, 2, . . . , r-1
Proof (by strong induction)
Let P(n) be the statement that n can be written in the form
n = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
Basis step:
If n = 1, then n = cr.2r = c0, where r = 0, and c0 = 1
Hence the statement is true for n = 1, i.e. P(1) is true
Existence of Binary Integer Representation
Inductive Hypothesis:
Let us suppose that statement is true for all i, 1 ≤ i < k,
i = ck.2k + ck-1.2k-1 + . . . + c1.21 + c0
cr.= 1, and cj = 0 or 1, j = 0, 1, 2, . . . , r-1
Show that
Now we prove that statement is true for k
Case 1
Suppose k is even, k/2 is an integer and k/2 < k, hence
k/2 = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
where r is non-negative integer and
cr.= 1, and cj = 0 or 1, j = 0, 1, 2, . . . , r-1
Existence of Binary Integer Representation
k = 2.cr.2r + 2.cr-1.2r-1 + . . . + 2.c1.21 + 2.c0
k = cr.2r+1 + cr-1.2r + . . . + c1.22 + c0.21, true
which is the required form
Case 2
Let k ≥ 3, is odd, (k-1)/2 is an integer and 1 ≤ (k-1)/2 < k,
(k-1)/2 = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
where r is non-negative integer and
cr.= 1, and cj = 0 or 1, j = 0, 1, 2, . . . , r-1
Now, k – 1 = cr.2r+1 + cr-1.2r + . . . + c1.22 + c0.21
And, k = cr.2r+1 + cr-1.2r + . . . + c1.22 + c0.21 + 1, true
Hence by strong mathematical induction, P(n) is true
Uniqueness
Uniqueness
Now we prove that n has a unique representation
n = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
Where r is non-negative integer
cr.= 1, and cj = 0 or 1, j = 0, 1, 2, . . . , r-1
On contrary, suppose that n has two different representations,
i.e.
n = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0 (1) and
n = br.2r + br-1.2r-1 + . . . + b1.21 + b0 (2)
Now subtract (2) from (1) we get
0 = (br- cr)2r + (br-1- cr-1).2r-1 + . . . + (b0- c0)
br = cr, br-1= cr-1, . . ., b1 = c1.and b0 = c0 , proved
More Complicated Example
1
Problem
Let f0 ( x ) = , and fn +1 = f0 fn , n 0.
2− x
Find an expression for fn and prove it by induction.
Solution
1
Since f 0 = and f n +1 = f o f 0 therefore
2− x
1 1 2− x
f1 ( x) = f 0 f 0 (x) = f 0 ( )= =
2− x 2−
1 3 − 2x
2− x
2− x 1 3 − 2x
And, f 2 ( x) = f 0 f1 (x) = f 0 ( )= =
3 − 2x 2 − x 4 − 3x
2−
3 − 2x
More Complicated Example
3 − 2x
And, f 3 ( x) = f 0 f 2 (x) = f 0 ( )
4 − 3x
1 4 − 3x
= =
3 − 2x 5 − 4x
2−
4 − 3x
And so on n − (n − 1) x
f n ( x) = f 0 f n -1 (x) = f 0 ( )
(n + 1) − nx
1 (n + 1) − nx
= =
n − (n − 1) x (n + 2) − (n + 1) x
2−
(n + 1) − nx
More Complicated Example
Now generalized function is
(n + 1) − nx
f n ( x) =
(n + 2) − (n + 1) x
f n +1 = f 0 f n f k +1 = f 0 f k k 0
By definition:
(k + 1) − kx 1
f k +1 ( x) = f 0 ( )=
(k + 2) − (k + 1) x (k + 1) − kx
2−
(k + 2) − (k + 1) x
(k + 2) − (k + 1) x
After simplifica tion, f k +1 ( x) = , proved.
(k + 3) − (k + 2) x